Decarbonized Energies and the Wealth of Three European Nations: A Comparative Nexus Study Using Granger and Toda-Yamamoto Approaches - Simionescu, Mihaela; Schneider, Nicolas; Gavurova, Beata (Frontiers in Environmental Science, 2022)
Considering the actual debate nuclear vs renewable that divides the green transition of the EU member states, this paper investigates the dynamic interactions between two sources of decarbonized energy (renewables and nuclear) and economic growth for three distinct economies: France, Spain, and Germany, all differing in their respective long-run nuclear planning. A complex methodological framework is employed to consider stationary (Augmented Dickey-Fuller test, Phillips-Perron test, Dickey-Fuller test, Elliott-Rothenberg-Stock test, Kwiatkowski-Phillips-Schmidt-Shin test, Zivot and Andrews test with structural break), cointegration (Johansen and Juselius test of cointegration, Gregory and Hansen cointegration test with breaks based on regime-trend shifts), long-run convergence (Vector Error Correction Model), causality (Granger causality test, Toda-Yamamoto non-causality test, and variance analysis (Impulse Response Functions) Empirical results for the period 1983–2019 fail to support the existence of statistical causality between renewable energy use and economic growth in France and Spain, which is congruent with the “neutral hypothesis”. Besides, while a weak one-way link is revealed from renewable energy use to GDP in Germany only, economic growth is found to substantially trigger nuclear energy consumption in Spain but not vice versa, thus corroborating the “growth hypothesis”. Accordingly, country-specific insights are provided to deploy low-carbon sectoral facilities in Spain, enhance the channels of radioactive waste treatment in France, and secure the nuclear phase-out in Germany.